Nitric Oxide Regulates the Ralstonia solanacearum Type III Secretion System - Connor G. Hendrich; Alicia N. Truchon; Beth L. Dalsing; Caitilyn Allen (Molecular Plant-Microbe Interactions, 2023)
Ralstonia solancearum causes bacterial wilt disease on diverse plant hosts. R. solanacearum cells enter a host from soil or infested water through the roots, then multiply and spread in the water-transporting xylem vessels. Despite the low nutrient content of xylem sap, R. solanacearum grows very well inside the host, using denitrification to respire in this hypoxic environment. R. solanacearum growth in planta also depends on the successful deployment of protein effectors into host cells via a type III secretion system (T3SS). The T3SS is absolutely required for R. solanacearum virulence, but it is metabolically costly and can trigger host defenses. Thus, the pathogen's success depends on optimized regulation of the T3SS. We found that a byproduct of denitrification, the toxic free-radical nitric oxide (NO), positively regulates the R. solanacearum T3SS both in vitro and in planta. Using chemical treatments and R. solanacearum mutants with altered NO levels, we show that the expression of a key T3SS regulator, hrpB, is induced by NO in culture. Analyzing the transcriptome of R. solanacearum responding to varying levels of NO both in culture and in planta revealed that the T3SS and effectors were broadly upregulated with increasing levels of NO. This regulation was specific to the T3SS and was not shared by other stressors. Our results suggest that R. solanacearum may experience an NO-rich environment in the plant host and that this NO contributes to the activation of the T3SS during infection. [Graphic: see text] Copyright © 2023 The Author(s). This is an open access article distributed under the CC BY 4.0 International license.